Supplementation of organic acid blends in water improves growth, meat yield, dressing parameters and bone development of broilers (Bangladesh Journal of Animal Science, 2016)
The present study was conducted in order to examine the effects of supplementing two liquid organic acid blends on growth performance, meat yield, dressing parameters, organ weights and bone development of broilers. A total of 120 broiler chicks were assigned to five dietary treatments in four replications with six birds per replication over a period of 5 weeks, following a completely randomized design. Dietary groups included; Control = Without organic acids; AW-C = Activate continuous administration; AW-P = Activate periodic administration; N-C = Nutrilac continuous administration; N-P = Nutrilac periodic administration. Results indicated that supplementation of organic acids improved (P